1988
DOI: 10.1128/aem.54.6.1414-1419.1988
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial metabolism of carbofuran

Abstract: Fifteen bacteria capable of degrading carbofuran (2,3-dihydro-2,2-dimethyl-7-benzofuranyl methylcarbamate) were isolated from soil samples with a history of pesticide application. All isolates were gram negative and were oxidase- and catalase-positive rods; they occurred singly or as short chains. All of the identified isolates belonged to one of two genera, Pseudomonas and Flavobacterium. They were separated into three groups based on their mode of utilization of carbofuran. Six isolates were placed in group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 21 publications
4
47
1
Order By: Relevance
“…Pseudomonas sp. 50432 [22] was maintained and grown in Luria-Bertani medium with less than usual NaCl (1 g of NaCl, 10 g of tryptophan and 5 g of yeast extract, pH 7.0) or minimum medium (MM) containing 4. 8 3 .…”
Section: Organism and Culture Conditionsmentioning
confidence: 99%
“…Pseudomonas sp. 50432 [22] was maintained and grown in Luria-Bertani medium with less than usual NaCl (1 g of NaCl, 10 g of tryptophan and 5 g of yeast extract, pH 7.0) or minimum medium (MM) containing 4. 8 3 .…”
Section: Organism and Culture Conditionsmentioning
confidence: 99%
“…It is now generally accepted that adapted soil microorganisms are responsible for the rapid degradation of soilapplied pesticides following repeated treatments with the same or similar compounds (Racke and Coats 1990). Several authors have reported the isolation and characterization of carbofuran-degrading fungi (Williams et al 1976), actinomycetes (Williams et al 1976 ;Venkateswarlu andSethunathan 1984, 1985) and bacteria belonging to several different genera (Felsot et al 1981;Rajagopal et al 1984;Karns et al 1986;Chaudry and Ali 1988;Ramanand et al 1988;Head et al 1992;Parekh et al 1992). Other workers have used several different enrichment techniques and have usually succeeded in isolating only one or two types of carbofuran-degrading bacteria from any one soil.…”
Section: Carbofuranmentioning
confidence: 99%
“…It is also degraded in soil and water by hydrolysis, photolysis and photodecomposition, yielding 2-hydroxyfuradan and furadan phenol [9]. Furthermore, the hydrolysis of carbamate esters, carbamate side chains and carbofuran phenol has also been reported [6,10,11]. Interestingly, our earlier studies on pesticide degraders have suggested their innate capability of simultaneous expression of ancillary traits along with the pesticide biodegradation potential [12,13].…”
Section: Introductionmentioning
confidence: 99%